Humoral Immune Response against Infectious Bursal Disease Using Live Attenuated, Live Immune Complex and Recombinant Vaccines in Broilers with High Maternal Derived Antibody Level - Ruenphet, Sakchai; Paditporn, Kornkamon; Mitchaothai, Jamlong (Journal of Mahanakorn Veterinary Medicine, 2017)
The aim of present study was to evaluate the immunological response of 3 difference Infectious bursal disease (IBD) vaccines in broiler chickens, even with high maternal derived antibody level. One thousand and two hundreds1-day-old broilers were divided into 4 groups. The chickens in the first group were unvaccinated with any IBD vaccine. The chickens in the second were vaccinated by the use of live attenuated vaccine Winterfield 2512 strain in drinking water at 2-week-old. The chickens in the third and fourth groups were vaccinated with live immune complex and recombinant vaccines by subcutaneous injection at 1-day-old, respectively. Chicken blood samples were collected at 1-day-old chick, once a week after vaccination and weekly until slaughtering. Subsequently, IBD antibody titer levels were measured by using enzyme-linked immunosorbent assay (ELISA) method. The chickens were vaccinated with both live immune complex-, as well as recombinant-vaccinated showed statistically significant high immune response compared with those in the unvaccinated group. However, all 5-week-old vaccinated chickens showed no difference of IBD antibody titer level. In addition, Bursa of Fabricius to body weight (B:BW) ratio at 5-week-old, were showed to be 1.30±0.49, 1.35±0.72 1.32±0.54 and 1.64±0.44 for the first to fourth group respectively, meaning that this parameter did not interfere with the Bursa of Fabricius developing after IBD vaccination. The present study indicated that all tested types of IBD vaccine generated significant responsiveness in term of humoral immunity and did not impair the Bursa of Fabricius development, even in the presence of high level of maternal derived antibody in broilers.